(untitled) (diségno, 2022)
The article presents the study, interpretation and organization process of the photographic archive of the Museo Egizio, Torino to support research and dissemination. Within this framework, the digitization process played a crucial role designing customized documentation and representation strategies to implement the consultation and management of the museum archive. This article highlights the role of the archive as historical memory able to communicate the transformations of methods and techniques for the documentation and representation between the XIX and the XX century. The archive provides information on the excavation process, as well as on the survey and representation tools. This material allows a better understanding and a correct interpretation of the documents produced in a given historical period on specific buildings, by allowing the identification of interventions of restoration and reconstruction, as well as displacement and excavations. The management of the digitized archive material was implemented thanks to a dedicated software, which automated and streamlined the work. The publication of the photographic archive was achieved through the customized web platform “The Photographic Archive of Museo Egizio”. In this process, the role of representation discipline has been fundamental in investigating, interpreting and communicating this rich and little-known archive, activating further knowledge processes that may enrich our understanding of cultural heritage.